The Role of Dialogic Patrols by the Cirebon City Police Sabhara Unit to Prevent Theft Crimes in the Context of Creating Harkamtibmas - Rahmad Andhira Fajri (Tanggon Kosala, 2021)
Crimes against Motorized Vehicle Theft in the Cirebon Regional Police Region Patrol Dialogue is a precautionary measure carried out by the Sabhara unit because in it there is a patrol dialogue in its implementation that involves directly with the community. In this research the reference library is the thesis of AKPOL cadet class 49 of 2018 Aditya Rizki Ridhotomo with a discussion about discussing vehicle prevention in Tarogong Kidul The concept used is the concept of patrol and for the theory of using routine activities, Role Theory and Management Theory which will be used in the formulation of the problem. The research method uses qualitative obtained with the findings, observations, study documents, and interviews with information sources. Techniques used for data analysis include data reduction, data presentation, drawing conclusions and verification to construct working hypotheses. Patrol dialogue by sabhara units in Cirebon City Police, such as the limitations of Sabhara unit members, requires knowledge of sabhara members in carrying out a task, supported by Patrols well in the community in the city of Cirebon. Helping members of the Indonesian National Police in maintaining the safety of other goods. Based on the results of the writing, the writer asks the members of the Sabhara Unit to cooperate with other units to help cover the Cirebon City Police jurisdiction. Researchers also help to be able to lead education to carry out vocational education to increase their knowledge in carrying out their responsibilities.